A-104 Comorbidities and Hepatitis C. (January 2016) - Sherman, Kenneth
Abstract : While most HCV literature focuses on liver injury and fibrosis progression, a spectrum of systemic disease processes, collectively called C hepatitis- associated systemic manifestations (CHASM), are present in a high proportion of infected persons. These include thyroid disease (Hashimoto's thyroiditis, Grave's disease, and thyroid cancer), cardiovascular disease (atherosclerosis, carotid artery disease, and coronary artery disease), renal disease (MPGN and glomerulosclerosis), eye disease (Mooren's ulcers and sicca syndrome), skin disease (PCT, vasculitis, and lichen planus), lymphomas (NHL and splenic T-cell), and diabetes. Mechanistic understanding of how HCV leads to CHASM processes could lead to development of new interventions. The role of early HCV treatment and cure may result in preventive strategies for a variety of complex disease states. Indeed data strongly supports decreases in all-cause mortality independent of liver disease when HCV cure is achieved. However, some conditions are mediated through autoimmune loop mechanisms and may be less responsive to HCV treatment.